Environmental, Social, Governance (ESG) Performance And Dividend Policy In Companies Listed on The Indonesia Stock Exchange - Muhammad Shahal Ghibran; Kurniawan, Meinanda (Integrasi Sains Media, 2024)
This study aims to determine the effect of environmental, social, and governance on dividend policy. This research was conducted using quantitative methods with the population taken was companies listed on the Indonesia Stock Exchange in 2017 - 2022. The sample in this study used 38 companies that had been selected by purposive sampling method. This type of research data is secondary data which has data sources from the Thomson Reuters Eikon database. The analysis technique used in this research is panel data regression using the lagrange test, the common effect model is selected, then the coefficient of determination (R^2) analysis is carried out, hypothesis testing with the use of partial tests (t test), and simultaneous tests (F test). The results of this study indicate a positive relationship between environmental and dividend payout ratio and a negative relationship between governance and dividend payout ratio.